Pengaruh Kualitas Pelayanan, Persepsi Harga dan Kualitas Produk terhadap Kepuasan Pelanggan - Farrel Rafie Indrawan; Rahmad Hartono (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
The current competitive conditions in the culinary business world require business actors to be more sensitive and pay attention to various factors that can influence customer satisfaction. Customer satisfaction is a very crucial aspect, because satisfied customers tend to return and make repeat purchases, which ultimately supports the sustainability and development of the business. This study aims to analyze and test the influence of three main variables, namely service quality, price perception, and product quality, on the level of customer satisfaction at Beranda Artotel Mangkuluhur. The population in this study were all guests who had visited the place, with sampling using a non-probability technique and involving 110 respondents who were willing to fill out the research questionnaire. Data analysis was carried out using the multiple linear regression method processed using SPSS software version 25. A series of tests were conducted to ensure the reliability and validity of the data, including validity tests, reliability tests, classical assumption tests, partial tests (t-tests), simultaneous tests (F-tests), and coefficient of determination tests. The results of the study indicate that partially, each variable of service quality, price perception, and product quality has a positive influence on customer satisfaction, where service quality has the most significant impact. Taken together, these three variables have also been shown to significantly influence customer satisfaction. Furthermore, the coefficient of determination of 97.8% indicates that almost all of the variation in customer satisfaction levels can be explained by the three factors studied